Job’s Satisfaction among Trainers of Public Vocational Training Institutes in Greece - Bakirtzoglou, Panteleimon; Ioannou, Panagiotis (Journal of Education and Vocational Research, 2017)
Abstract: The purpose of the present study was to investigate the effect of the personnel, interpersonal and organizational factors in job satisfaction among trainers of public Vocational Training Institutes in the city of Thessaloniki. Sample consisted of 300 adults’ trainers with a mean age of 40.3 years. Job’s satisfaction was used as an independent variable while as dependent variables personnel(age, sex, educational level, marital status, number of children, educational level, profession and teaching experience), interpersonal (relationships with trainees, relationships with co-educators, relationship with the administration, personal development and professionalism) and organizational factors (salary, building structure and working conditions) were used. Statistical analysis included the use of correlation and regression analysis. Results showed that from the dependent variables only age (r=.342), years of working experience in Vocational Training Institutes (r=.296), relationship with the administration (r=.699) and working conditions (r=.690) had a significant relationship with adults’ trainers’ job satisfaction (p<0.01). Furthermore regression analysis showed that relationship with the manager had the biggest prediction of trainers’ total job satisfaction at a percentage of 48.6% (r=.699, p<0.01), working conditions can predict trainers’ job satisfaction at a percentage of 47.7% (r=.690) and age and teaching experience can predict trainers’ total job satisfaction at a percentage of 20% (r=.014, p<0.05). In conclusion adults’ trainers’ total job satisfaction in Vocational Training Institutes in Greece, is influenced mostly by interpersonal (relationship with the administration) and organizational factors (working conditions). Keywords: Administration, working conditions, teaching experience, vocational education, adults